Stadtklimatische Effekte der raum-zeitlichen Niederschlagsverteilung aufgezeigt am Beispiel von Mexiko-Stadt - Jauregui, Erneso; Klaus, Dieter (ERDKUNDE, 1982)
Precipitation analysis using urban/rural precipitation ratio for Mexico City is used to detect time trends in urban effects. A steady increase in rainfall amounts (since the 1940’s) is apparent from this analysis. At the same time amounts of precipitation seem to have decreased to the windward and the leeward side of this tropical city in relation to the east winds of the rainy season. Precipitation increase in the urban area is accompanied by a rise in the frequency of heavy rains. In wet years there is evidence of a marked preference of precipitation for falling during weekdays. The city’s aerosol production, too, shows maximum values towards the middle and end of the week. In dry years a weekend reduction in aerosols apparently favours additional amounts of precipitation. Genetic relationships are discussed.